The equalizer. Season one [videorecording (DVD)] - Queen Latifah, 1970-; Kittles, Tory; Goldberg, Adam, 1970-; Lapira, Liza; Hayes, Laya Deleon; Toussaint, Lorraine, 1960-; Noth, Chris, 1954- (Paramount Home Entertainment, 2021)
Robyn McCall, an enigmatic woman with a mysterious background, uses her extensive skills to help those with nowhere else to turn. McCall comes across to most like an average single mom who is quietly raising her teenage daughter. But to a trusted few, she is 'The Equalizer,' an anonymous guardian angel and defender of the downtrodden, who's also dogged in her pursuit of personal redemption.